Access to languages other than English in Australian universities: an educational pipeline of privilege. Issue 2 (23rd February 2019) - Molla, Tebeje; Harvey, Andrew; Sellar, Sam
ABSTRACT: This article explores factors contributing to unequal patterns of access to languages other than English (LOTE) in Australian universities. A critical analysis of qualitative and quantitative data generated through interviews, surveys and document analysis reveals that underrepresentation in LOTE courses in Australian universities is attributable to: (a) unequal access to LOTE learning areas at the school level; (b) low tertiary entrance scores that do not grant access to elite universities that offer broad LOTE course options; (c) differential prior international learning experiences that inform dispositions towards intercultural competence, including proficiency in LOTE; and (d) limited provision of LOTE courses in regional university campuses. We conclude that access to foreign language courses in Australian universities is not equitable, and in the context of globalisation opportunities, this poses a risk of reproducing social disadvantage alongside other structural factors such as socio-economic status and regional background.